An Investigation into the Effects of Martial Arts Training on Impulsive Consumer Behavior - Dimas Budi Prasetyo; Paloma Mari-Beffa (ANIMA Indonesian Psychological Journal, 2019)
Consumer impulsiveness is an enticing topic regarding consumer behavior, and methods of avoiding such impulsiveness (through nurturing self-control) have been considered virtuous, mainly to achieve better long-term goals. Past studies show that self-control has been developed not only through a systematic theoretical framework but also neurologically. Martial arts (MA) training involves mind and body coordination, which is beneficial for nurturing concentration and self-control. The present study investigated the influence of martial arts training on individual capacity to avoid impulsive consumer behavior. Sixty-seven students joined in the study, in three different groups: (1) practitioners of martial arts (MA Group); (2) non-practitioners of martial arts (Non-MA Group); and (3) lapsed practitioner of martial arts (Lapsed-MA Group). The scale consisted of two separate subscales: (1) Consumer Impulsiveness Sub-scale (CIS); and (2) (Lack of) Premeditation Sub-scale. The study used some correlation methods, the ANCOVA method, and a hierarchical multiple linear regression analysis. Results showed that all three groups were prudent in their thinking processes and abilities to resist temptation. In the martial arts and ex-martial arts groups, the more frequent individual training (current training for the MA Group and in the past for the Lapsed MA Group), and the higher the ranks they achieved, significantly predicted their lower propensity towards impulsiveness in their consumer habits.